2019
DOI: 10.11613/bm.2019.020710
|View full text |Cite
|
Sign up to set email alerts
|

Elevated activated partial thromboplastin time-based clot waveform analysis markers have strong positive association with acute venous thromboembolism

Abstract: Introduction: A hypercoagulable state is a predisposition for venous thromboembolism (VTE). The activated partial thromboplastin time (aPTT)-based clot waveform analysis (CWA) is a global haemostatic measure but its role in assessment of hypercoagulability and thrombotic disorders is uncertain. We aimed to study the changes of CWA parameters in acute VTE. We hypothesized that patients with acute VTE would demonstrate higher CWA values than control patients without VTE and having elevated CWA parameters is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…The higher min1 value could possibly suggest an overall elevated prothrombotic state in COVID-19 infection given our previous finding that min1, in comparison to min2 and max2, is more strongly associated with thrombotic events. 5 Consistent with published reports, 4 all the patients expressed high CRP levels even on initial assessment during hospitalization, while procalcitonin remained unremarkable (data not shown). We did not observe a definitive pattern of association between CRP and ICU admission -patient 3 had a CRP upon ICU admission that was lower than that of patient 1 upon initial hospitalization.…”
Section: O R R E S P O N D E N C Esupporting
confidence: 91%
See 1 more Smart Citation
“…The higher min1 value could possibly suggest an overall elevated prothrombotic state in COVID-19 infection given our previous finding that min1, in comparison to min2 and max2, is more strongly associated with thrombotic events. 5 Consistent with published reports, 4 all the patients expressed high CRP levels even on initial assessment during hospitalization, while procalcitonin remained unremarkable (data not shown). We did not observe a definitive pattern of association between CRP and ICU admission -patient 3 had a CRP upon ICU admission that was lower than that of patient 1 upon initial hospitalization.…”
Section: O R R E S P O N D E N C Esupporting
confidence: 91%
“…Many of the levels were at least as high as what we noted in acute venous thromboembolism, which had an odds ratio of four or greater for thrombotic events. 5 Of note, although none of our cases…”
Section: O R R E S P O N D E N C Ementioning
confidence: 54%
“…To further evaluate the thrombotic potential in COVID-19, we analysed available CWA parameters as a global haemostatic assessment. It has been reported that CWA parameters differ in various types of infections 34 and increased CWA is associated with hypercoagulability 35 , 36 . Our findings suggest that there were no significant changes in the overall haemostatic functions in mild COVID-19 but severe COVID-19 was associated with a prothrombotic state and this hypercoagulability gradually normalizes during the convalescent phase.…”
Section: Discussionmentioning
confidence: 99%
“…Our study further supports the available evidence that severe SARS-CoV-2 infection is associated with hypercoagulability [ 7 , 21 ]. Clot waveform analysis (CWA) has not been well described as a tool to evaluate a hypercoagulable state, although emerging literature shows promising evidence that this may be useful in predicting for VTE [ 22 ] and also in several procoagulable states [ 23 , 24 ]. CWA showed a hypercoagulable state with increased parameters of clot maximum velocity (min1), clot maximum acceleration (min2), clot maximum deceleration (max2) and delta change (decreased light transmission reflective of increased clot thickness) characterizing a hypercoagulable state in 10 patients (with corresponding raised Factor VIII, vWF antigen, D-dimer and fibrinogen levels), with no evidence of concurrent bacterial infection at the time of assessment.…”
Section: Discussionmentioning
confidence: 99%